Esterification of Waste Cooking Oil Using Heterogeneous Catalyst: An Experiment for The Catalytic Chemistry Laboratory - Purwasusanti, Nungky; Ediati, Ratna (IPTEK Journal of Proceedings Series, 2015)
The basic concept of the use of catalysts can be studied in the course of chemical catalysts. The use of heterogeneous catalysts offers many advantages, such as: the catalyst can be easily separated from the reaction mixture without the use of solvent. Chemical catalyst can be studied through experiments of esterification reaction of waste cooking oil with methanol using heterogeneous catalyst in the process of making biodiesel. Esterification results showed that the highest conversion (83%) was obtained by metakaolin catalyst at a reaction temperature of 160 Â°C for 2 hours at oil to methanol ratio of 1:30.